Modulation of biofilms by microbial potential consortia of human: conception of extended probiotic compartment of biotope, prognostic patterns - V. M. Lakhtin; A. L. Bajrakova; M. V. Lakhtin; A. V. Aleshkin; S. S. Afanasiev; V. A. Aleshkin (Acta Biomedica Scientifica, 2013)
The purpose of the investigation was development of screening visual and quantitative method of strain selection and potential consortium of normal human microflora (including one of probiotic orientation) for future creation of new synbiotic, symbiotic and acellular prophylactic and medicinal forms significant for therapy of endoceliac diseases. We used strains of yeast Candida and lactobacilli Lactobacillus, isolated from normal microflora of urogenital biotope of healthy donors. Suspensions of strains with turbidity 1 unit of Mcfarland standards were added with increasing doses to wells of polystyrene micropanels with surplus of MRS broth (variants A, B, C, D and E) and incubated 48 hours at 37 °C. Cultivated biofilms were stained with gentian violet and bottoms of wells in micropanels were photographed and scanned. Optical density of ethanol fixated stained biofilms in wells was registered with colour filter 620 nm. Visual evaluation was performed of influence of biofilm resolving activity and opposite action of polysaccharides and other adhesins. To assess ranging of expressiveness if biofilms growth in monocultures we suggested to use calculated coefficient (D + E)/(B + C), which reflects rectifying and decreasing of gradient of slope of dosage dependence of optical density in series of cultivations of microbial suspensions. The results make possible to perform monitoring of early film formation by strains of microorganisms and their mixtures. Micropanel is convenient for getting prognostic patterns of interference on film formation of co-existing in biotope consortiums of microorganisms populations and for evaluation of health status of biotope human microbiocenosises. It is possible to select strains biocompatible with human organism and their mixtures of probiotic orientation which are of great interest for prevention and therapy antibiofilm, antipathogenic, enzymatic, alternative to antibiotics, supporting adjuvant and combined